Uptake and translocation of pharmaceutically active compounds by olive tree (Olea europaea L.) irrigated with treated municipal wastewater - Mininni, Alba N.; Pietrafesa, Angela; Calabritto, Maria; Di Biase, Roberto; Brunetti, Gennaro; De Mastro, Francesco; Murgolo, Sapia; De Ceglie, Cristina; Salerno, Carlo; Dichio, Bartolomeo (Frontiers in Plant Science, 2024)
The use of treated municipal wastewater (TWW) represents a relevant opportunity for irrigation of agricultural crops in semi-arid regions to counter the increasing water scarcity. Pharmaceutically Active Compounds (PhACs) are often detected in treated wastewater, posing a risk to the human and environment. PhACs can accumulate in soils and translocate into different plant tissues, reaching in some cases edible organs and entering the food chain. This study evaluated the uptake and translocation processes of ten PhACs by olive trees irrigated with TWW, investigating their accumulation in different plant organs. The experiment was conducted in southern Italy, in two-year-old plants irrigated with three different types of water: freshwater (FW), TWW spiked with 10 PhACs at the concentration of 200 µg L-1 (1X TWW) and at a triple dose (3X TWW), from July to October 2021. The concentration of PhACs in soil and plant organs was assessed, collecting samples of root, stem, shoot, leaf, fruit and kernel at 0 (T0), 50 (T1), 107 (T2) days of irrigation. PhACs extraction from soil and plant organs was carried out using the QuEChERS method and their concentrations were determined by high-resolution mass spectrometry coupled with liquid chromatography. Results of Uptake Factors (UF) showed a different behavior between compounds according to their physico-chemical properties, highlighting PhACs accumulation and translocation in different plant organs (also edible part) in 1X TWW and 3X TWW compared to FW. Two PhACs, carbamazepine and fluconazole, showed interactions with the soil-plant-system, translocating also in the aerial part of the plant, with a Translocation Factor (TF) greater than 1, which indicates high root-to-leaf translocation. Findings highlight that only few PhACs among the selected compounds can be uptaken by woody plants and accumulated in edible parts at low concentration. No effects of PhACs exposure on plant growth have been detected. Despite the attention to be paid to the few compounds that translocate into edible organs, these results are promising for adapting wastewater irrigation in crops. Increasing knowledge about PhACs behavior in woody plants can be important for developing optimized wastewater irrigation and soil management strategies to reduce PhACs accumulation and translocation in plants.